Assessing the Mediating Role of Perceived Usefulness towards the Adoption of Financial Technology (FinTech) in Nepal - Bhatta, Sheena; Duwal, Bal Ram; Hakuduwal, Kishor (Nepal Journal of Multidisciplinary Research, 2025)
Background: In Nepal, the financial technologies (FinTech) sector is expanding rapidly, with 25.8 million digital wallet accounts and 26.5 million mobile banking accounts by mid-January 2025. Despite the swift proliferation of FinTech services in Nepal, widespread adoption has not yet been observed. While research has been done globally on FinTech adoption, there is limited research on drivers of adoption intention, including mediation effects in the Nepalese context. Objectives: The major objective of the study is to scrutinize the effect of trust; security & privacy; and perceived ease of use on the intention to adopt general FinTech services like mobile banking, digital wallets, or internet banking. It also assesses how perceived usefulness mediates the relationship between trust; security & privacy; perceived ease of use, and the intention to adopt FinTech. Design/Methodology/Approach: The present study adopted both the Theory of Reasoned Action (TRA) and the Technology Acceptance Model (TAM) as its theoretical base. The research is descriptive and explanatory research design. Employing convenience sampling, a total of 240 responses were collected, and the data were analyzed using Structural Equation Modeling with Partial Least Squares version 4.1.0.9. Findings: The outcomes of the study imply that perceived ease of use has a significant effect on both perceived usefulness and intention to adopt FinTech, and also mediates a strong indirect effect on intention to adopt through perceived usefulness. Trust and security & privacy do not have a significant direct or indirect effect on perceived usefulness and intention to adopt FinTech, suggesting these factors may not be as salient in the Nepalese context. Perceived usefulness is the strongest driver of adoption intention, demonstrating the importance of building user-friendly platforms that increase perceived usefulness to facilitate adoption. Research Ethics: The authors obtained informed consent from the survey participants, indicating their understanding of the research purpose, procedure, and voluntary participation. Data confidentiality of participants was maintained by using anonymity. Novelty: The study contributes by developing a more unified model for assessing user’ behavioral intention towards FinTech adoption in Nepal by adopting constructs from the TRA and TAM model. Trust and security & privacy are incorporated as extended variables to enhance the theoretical prospect of the existing literature.